Językowe sposoby wyrażania przyczynowości w tekście prawnym (na przykładzie kodeksu karnego z 1969 r.): [Linguistic methods of expressing causality in legal texts (on the example of the penal code of 1969)] (Studia Prawnicze / The Legal Studies, 1985)
In the doctrine of penal law offences are divided into effective and ineffective ones. In the former case, a condition of bearing responsibility by the perpetrator is the existence of( causative-effective link between the act. and criminal result defined by the law. Thus, the question of causality is very important in the doctrine of penal law. However, a question arises how the legislator expresses causality in legal texts, i.e. what are the linguistic methods of expressing it. The author of the article, on the basis of the Polish penal code, distinguishes three basic ways of expressing causality. The first method consists in expressing causality by means of sentences built according to the pattern "p i caus q". Another one consists in using the verb "cause" followed by an obligatory object denoting criminal result. Other verbs are also used to express causality but it is difficult to point to their special syntactic features. The author makes and considers a hypothesis that these verbs which contain a semantis component "cause" in their meaning are used to express causality and they may be found in provisions defining the types of effective offences,